Características e mecanismos de desgaste dos refratários MgO-C usados na linha de escória de panelas de aço - Leite, Frederico Concon (2013)
Steel ladles are special vessels used for liquid steel transportation from the primary refining stage up to its solidification one at the casting shop. The MgO-C bricks have been used for lining this equipment due to its high chemical resistance to steel slags and thermal shock. However, new procedures during refining stages have increased the attack of the refractory lining, especially in the slag line, where the corrosion and wearing processes are intense. This fact has significant implications in reducing the ladle availability, leading to the need of intermediary repairs, besides increasing production costs and affecting the operational safety. In this context, the present study aims to evaluate the wear mechanisms of the steel ladle slag line by identifying the effects of some variables during the refractory production, placing and operation. In order to achieve that, the computational thermodynamics was widely used to understand the reactions and transformations that occur in complex systems, such as the interaction between refractory and slag. The software helped in evaluating the effect of raw materials, antioxidants additives and alternative materials (such as spinel) of new MgO-C ceramic compositions performance. The laboratory tests indicated the oxidation and corrosion as the main wearing mechanisms in MgOC refractory. In the first case, it was detected the importance to develop solutions for carbon protection, such as, applying a lining antioxidant coating for the first ladle heating. In addition, the slag conditioning efficiency to reduce the bricks corrosion rate was attested, due to the chemical potential decrease for dissolving the refractory constituents. Thus, this project has improved the knowledge of MgO-C behavior at high temperatures and also helped in the development of alternative solutions (focused in operational standards and formulations) to maximize the refractory performance.